La prise de pouvoir par Louis XIV = [videorecording (DVD)] : The taking of power by Louis XIV - Patte, Jean-Marie; Jourdan, Raymond; Silvagni (Criterion collection ;, 2008)
Cardinal Mazarin dies in 1661. The young Louis asserts his intention to govern as well as rule. Mazarin's fiscal advisor, Colbert, warns against Fouquet, who wants to be prime minister and is looting the treasury. Fouquet believes Louis will soon tire of exercising power and overplays his hand. Louis' mistress reports this to the king who arrests Fouquet. Louis and Colbert design a brilliant strategy to keep merchants making money, nobles in debt, the urban poor working and fed, and peasants untaxed. Years later, in a coda, Louis exercises the power of the sun.